Effect of current density and alkaline pH on morphology and properties of electroplated Sn - Sharma, Ashutosh; Ahn, Byungmin (Materials Research Express, 2019)
The purpose of this research is to examine the effect of plating current density as well as bath pH on the morphology and solderability of Pb-free pure Sn, plated from alkaline baths on copper substrates. Pure Sn coatings were prepared from a plating electrolyte composed of sodium stannate, sodium hydroxide, and sorbitol as an additive. The bath pH was changed from 9 to 14 and the plating current density was varied from 5-25 mA cm-2. The solderability of the Sn platings was estimated by spread ratio measurement according to JIS-Z-3197 standard. The obtained coatings were polycrystalline having a tetragonal β-Sn structure. The deposits were spongy and porous at pH ≈ 9-10. As the bath pH was increased from 11-13, the film growth improved, the best crystallinity of film was obtained at pH 13 and a current density of 15-20 mA cm-2. The coatings possess optimum microhardness and spreadability at a current density of 15 mA cm-2 and bath pH ∼12-13. It is shown that the optimization of current density and bath pH is necessary for the better strength and solderability of Sn coatings when alkaline baths are employed.
Keywords: Alkaline baths; Copper substrates; Electro-plated sn; Polycrystalline; Pulse plating; Solderability; Spread ratio; Spreadability; coating; current density; growth; pulse plating; solder; tin